1975
DOI: 10.1037/h0077063
|View full text |Cite
|
Sign up to set email alerts
|

Isolation-induced aggression in newly hatched ducklings.

Abstract: Newly hatched Khaki Campbell ducklings (Anas platyrhynchos domesticus) were initially housed in pairs and subsequently transferred to isolated housing conditions. Subjects living with another bird displayed filial behavior and little aggression upon encountering another duckling in a test arena. In contrast, ducklings housed in isolation exhibited aggressive pecking in addition to filial behavior when another duckling was subsequently encountered. In Experiment 2, ducklings were housed with an imprinting objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1976
1976
1978
1978

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
3
18
0
Order By: Relevance
“…To investigate this issue we housed one group of paired subjects in a completely darkened room, thereby permitting tactile stimulation from conspecifics but not visual stimulation. housed in a single unit (128 X 36 X 65 cm) for a period of four days, under normal daylight illumination (previous work has indicated that with ducklings, aggression induced by prior isolation is reduced to a low level after four days of living with a conspecific; Hoffman et al, 1975). On the fifth day, the quail were randomly divided into three groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate this issue we housed one group of paired subjects in a completely darkened room, thereby permitting tactile stimulation from conspecifics but not visual stimulation. housed in a single unit (128 X 36 X 65 cm) for a period of four days, under normal daylight illumination (previous work has indicated that with ducklings, aggression induced by prior isolation is reduced to a low level after four days of living with a conspecific; Hoffman et al, 1975). On the fifth day, the quail were randomly divided into three groups.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than the lack of opportunity to dissipate an aggressive drive through social signals, the critical factor in isolation-induced aggression might instead be the lack of stimulation that would otherwise elicit attachment behavior (Hoffman et al, 1975). Visual stimulation is well known to have powerful effects in the attachment behavior of young precocial birds (Hoffman and Ratner, 1973), and recent evidence is beginning to suggest tactile stimulation as an important factor as well (Clements and Lien, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations